Implementation of Lean Six Sigma in Pharmaceutical Inventory Control at Hospitals: A Literature Review - Damput, Fransiska Satriani; Sulistiadi, Wahyu (Jurnal Health Sains, 2025)
Controlling drug inventory in hospitals plays an important role in ensuring the continuation of safe, timely, and efficient health services. However, problems such as overstock, out-of-stock, and inefficiency of the distribution process are often the main obstacles that still occur frequently. Lean Six Sigma in drug inventory control in hospitals is an approach that combines Lean and Six Sigma principles to improve efficiency, reduce waste, and decrease variation in the drug management process. The implementation of Lean Six Sigma aims to overcome problems such as stock out, overstock, and inefficient drug purchases, thereby improving the quality of pharmaceutical services in hospitals. Methods: This literature study used a combination of keywords "six", "sigma", lean", "inventory", "pharmacy", "hospital" and "Indonesia" in three databases ProQuest, ScienceDirect and Google Scholar. With the guidance of PRISMA, the selection of research articles that meet the inclusion and exclusion requirements is carried out. Results: Using the PRISMA guide, 6703 articles were found from the combined keywords. After screening for conformity with the inclusion and exclusion criteria, only 5 research articles were found that explained the implementation of lean six sigma in the pharmaceutical inventory supervision area in hospitals. From the five research articles, there are several implementations of lean six sigma such as DMAIC, 5 R's, Pareto Chart, Turnover Ratio, and waste analysis. Conclusion: Several methods of implementing lean management can be applied in pharmaceutical logistics to improve inventory oversight in pharmaceutical logistics.